PERAN PROGRAM PENGENALAN DALAM MENINGKATKAN ENGAGEMENT KARYAWAN: PENDEKATAN BERBASIS TEORI MOTIVASI - Hidayat, Raihan Zaky Maulana; Robbina, Maharani Adie Firyal Rohmatu; Sari, Erika Novita; Azizah, Winayatun; Iskandar, Ahmad Faurocky (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Companies need to have quality employees who can play an active role in dealing with various problems, therefore, the induction program is a stimulus and has an important role in increasing employee engagement in an organization. This research aims to find out the impact of an orientation program with a motivational approach on employee involvement in a company. This type of research uses a qualitative descriptive method, which describes in detail or describes the phenomena that occur. The data collection method uses library research (library study). The results of the research show that developing the management of human resources, especially employees through an introduction program, this program indirectly has benefits for the company so that they can get a sense of attachment earlier from new employees so that the company can maintain its human resources. , and minimize turnover